Development of a portable reverse transcription loop‐mediated isothermal amplification system to detect the E1 region of Chikungunya virus in a cost‐effective manner. (22nd July 2020) - Saechue, Benjawan; Kamiyama, Naganori; Wang, Yinan; Fukuda, Chiaki; Watanabe, Kei; Soga, Yasuhiro; Goto, Mizuki; Dewayani, Astri; Ariki, Shimpei; Hirose, Haruna; Ozaka, Sotaro; Sachi, Nozomi; et al.
Abstract: Chikungunya fever is a mosquito‐borne disease cause of persistent arthralgia. The current diagnosis of Chikungunya virus (CHIKV) relies on a conventional reverse transcription polymerase chain reaction assay. Reverse transcription loop‐mediated isothermal amplification (RT‐LAMP) is a rapid and simple tool used for DNA‐based diagnosis of a variety of infectious diseases. In this study, we established an RT‐LAMP system to recognize CHIKV by targeting the envelope protein 1 (E1) gene that could also detect CHIKV at a concentration of 8 PFU without incorrectly detecting other mosquito‐borne viruses. The system also amplified the E1 genome in the serum of CHIKV‐infected mice with high sensitivity and specificity. Moreover, we established a dry RT‐LAMP system that can be transported without a cold chain, which detected the virus genome in CHIKV‐infected patient samples with high accuracy. Thus, the dry RT‐LAMP system has great potential to be applied as a novel CHIKV screening kit in endemic areas. Abstract : A portable, simple and cost‐effective dry RT‐LAMP system specific for the E1 region of CHIKV. Highly sensitive and specific to CHIKV, but not to other mosquito‐borne viruses. A rapid screening platform suitable for on‐site diagnosis to detect CHIKV in human clinical samples.